Chronic obstructive pulmonary disease and heart failure in real life: the tip of the iceberg in the sea of comorbidities. A prospective observational study - Para, Ombretta; Vanetti, Marco; Dibonaventura, Chiara; Salerno, Davide; Caruso, Lorenzo; Carleo, Christian; Raza, Asim; Nozzoli, Carlo; Spanevello, Antonio (Monaldi archives for chest disease, 2025)
Chronic obstructive pulmonary disease (COPD) and heart failure (HF) are two of the most common conditions treated in internal medicine. Although it is known that these diseases often coexist, the specific characteristics of the affected patients and the prognostic implications are not yet well understood. Managing patients with both COPD and HF requires an integrated treatment approach. The aim of the study was to examine the association between COPD and HF. We conducted a prospective observational cohort study. All consenting patients admitted to the Internal Medicine Department from the Emergency Department with known or strongly suspected COPD were enrolled. A total of 144 patients were included, with 47.2% of them also having HF, distributed among the various HF subcategories as follows: 10.4% with HF with reduced ejection fraction (HFrEF), 3.5% with HF with mild-reduced ejection fraction, and 33.3% with HF with preserved ejection fraction (HFpEF). This result is consistent with the literature, which suggests a higher prevalence of COPD in patients with HFpEF compared to HFrEF. A Doppler echocardiography was performed during hospitalization. Some variables showed a statistically significant difference when comparing patients with COPD and HF to those with COPD without HF. Interestingly, the follow-up at 3 and 6 months post-discharge revealed higher mortality in patients with HF, with an odds ratio (95% confidence interval) of 10.0 (1.2-82.2). This study could contribute to a better understanding of the prognostic implications arising from the coexistence of COPD and HF, emphasizing the importance of a patient-centered approach in managing multiple comorbidities.